Manegement of Dystocia due to Acute Extreme Lateral Deviation of Head and Neck in Cattle: A Case Report - Singh, Kiran; Biswas, Newton; Sushil Kumar; Neeraj Srivastava; Khan, M H (Animal Reproduction Update, 2024)
A primiparous five-year-old non-descript cow was presented to the Referral Veterinary Polyclinic, ICAR-IVRI, with a history of complete gestation, frequent straining, rupture of the water bag without any further progress in labor since the last 12 hours, and a failed attempt of manual foetal extraction by the local veterinarian. After conducting a general clinical examination, all the vital parameters were recorded. A per-rectal examination followed by a per-vaginal examination was carried out to determine the presentation, position, and posture of the foetus. The foetal forelimbs were lying in the birth canal, although the foetal head and neck were extremely deviated laterally and lodged very deep in the uterus around the hind limbs. Different obstetrical maneuvers were performed to correct the foetal disposition, followed by the successful extraction of a dead female foetus. The dam was stable and successfully given postoperative therapy. A follow-up had been carried out for up to one week, and the animal was recovered uneventfully.